Effect of six-week short-duration deep breathing on young adults with chronic ankle instability-a pilot randomized control trial - Vinodhkumar Ramalingam; Soon Keng Cheong; Poh Foong Lee (BMC, 2023)
Abstract Background Chronic ankle instability (CAI) is the most common injury in youth sports, which leads to psychological stress from doubting their performance. Cost effective and easy to access tool to reduce the stress among this target group are desired. Therefore, the purpose of this study was to investigate the effect of adding on intervention with short-duration deep breathing (SDDB) alongside with conventional physiotherapy (CP) among young adults with chronic ankle instability (CAI). Methods Total of 30 CAI participants attended physiotherapy, who were randomly assigned into control and experimental groups. The participants in the experimental group received combined intervention (SDDB + CP), and the control group received CP for 6 weeks. The effectiveness of interventions was assessed at 3 intervals with a battery of questionnaires (Visual Analog Score, Cumberland Ankle Instability Tool, Mindful Attention Awareness Scale, and Oxford Happiness Questionnaire) at the end of week 3, week 6, and week 12 as follow-up. A two-way repeated measures of ANOVA was applied to report the statistical significance at p < 0.05. Results The results showed a better improvement in pain, balance, happiness, and mindfulness attention among participants in the experimental group, with a significant improvement in mindful attention over the time point as compared to the control group. Conclusion The findings provide insight into incorporating SDDB additions to the existing CP for better CAI management. Breathing techniques that improve attention and happiness play a vital role in CAI, which recommends the biopsychosocial approach in chronic injury rehabilitation. Trial registration Current Controlled Trials using Clinical Trials Registry under ID number NCT04812158 retrospectively registered on 23/03/2021.